Buyer-supplier relationship on social sustainability: Moderation analysis of cultural intelligence - Usama Awan; Andrzej Kraslawski; Janne Huiskonen (Cogent Business & Management, 2018)
The aim of this study is to investigate moderating impact of cultural intelligence among relational governance and commitment to sustainability, consequently on the social sustainability performance. Relying on social exchange theory and dynamic capability view, we advance a more nuanced approach to examining how cultural intelligence interaction with relational governance enhances supplier's commitment to sustainability and hence allows suppliers firm to improve their social sustainability performance, based on data collected from 239 manufacturing firms located in Pakistan. Structural equation modelling and regression base moderation analysis supported the hypothesis. The results suggest that relational governance can act as centralised control for ensuring commitment to sustainability and social sustainability performance. Our results suggest that cultural intelligence moderates the relationship among relational governance and commitment to sustainability. Our study contributes to the debate about the relational governance in the achievement of commitment to sustainability that so far has never been investigated within manufacturing industry of Pakistan. The results of the research clearly show the positive impact of commitment on social sustainability performance. Theoretical contributions, managerial implications and future research direction also presented.
Keywords: 650